Effects of micronized-roasted coffee concentration and temperature process on technological properties of rice-based extruded (Research, Society and Development, 2021)
New ingredients have been used in extruded products to increase the healthiness and regionalization of these products. However, the process variables that can interfere with the technological quality of the product should be studied, aimed at good acceptance by consumers. This study aimed to evaluate the effects of the concentration of micronized roasted coffee (MRC) and the barrel temperature on the technological properties of rice-based extrudates. The extrudates were made with 3 and 8% MRC to replace rice flour and processed in a mono-extruder at 140 and 180 oC. They were characterized for color, expansion index, hardness, bowl-life, porosity, water absorption index, and solubility index, and paste properties. To assess the effects of the process variables, analysis of variance, and Scott-Knott test (p